Electronic spectra of ytterbium fluoride from relativistic electronic structure calculations. Issue 39 (1st October 2021) - Pototschnig, Johann V.; Dyall, Kenneth G.; Visscher, Lucas; Gomes, André Severo Pereira
Abstract : Potential energy curves for the YbF obtained by relativistic electronic structure methods are presented. Due to the difficulties of describing this system separate computations for open and closed f-shells were necessary. Abstract : We report an investigation of the low-lying excited states of the YbF molecule-a candidate molecule for experimental measurements of the electron electric dipole moment-with 2-component based multi-reference configuration interaction (MRCI), equation of motion coupled cluster (EOM-CCSD) and the extrapolated intermediate Hamiltonian Fock-space coupled cluster (XIHFS-CCSD). Specifically, we address the question of the nature of these low-lying states in terms of configurations containing filled or partially-filled Yb 4f shells. We show that while it does not appear possible to carry out calculations with both kinds of configurations contained in the same active space, reliable information can be extracted from different sectors of Fock space-that is, by performing electron attachment and detachment IHFS-CCSD and EOM-CCSD calculation on the closed-shell YbF + and YbF − species, respectively. From these calculations we predict Ω = 1/2, 3/2 states, arising from the 4f 13 σ26s, 4f 14 5d 1 /6p 1, and 4f 13 5d 1 σ16s configurations to be able to interact as they appear in the same energy range around the ground-state equilibrium geometry. As these states are generated from different sectors of Fock space, they are almost orthogonal and provide complementary descriptions of parts of the excited state manifold. To obtain a comprehensive picture, we introduce a simple adiabatization model to extract energies of interacting Ω = 1/2, 3/2 states that can be compared to experimental observations.